Hey folks,

i get very strange irf when i ran the following little monetary model. My problem is, when i look at the irf of U (the monetary shock) I would expect that when U rises R (the nominal interest rate) will also rise due to the standard taylor rule (R/Rss = (PI)^(jotaPI)*(Y/Yss)^(jotaY)*U;). But the opposite is the case. PLEASE WHERE IS THE MISTAKE?? Do I think wrong??

THE MODEL:

```
close all
var LAM R PI RK C W L Y A K MC B G U I RR TAX UTIL;
varexo eps_A eps_U eps_G;
parameters beta delta sigmaL omega alpha phiP Phi tau jotaR jotaPI jotaY rhoA rhoU rhoG sigmaA sigmaU sigmaG nu
TAXss Gss Yss Rss sc AUX Kss Lss Css Wss Iss RKss LAMss Ass Uss Bss t TAXBAR;
beta = 0.90;
delta = 0.025;
sigmaL = 5;
omega = 1;
alpha = 2/3;
phiP = 1.25;
Phi = 1.5;
tau = 5;
jotaR = 0;
jotaPI = 1.5;
jotaY = 0.125;
rhoA = 0.90;
rhoU = 0.90;
rhoG = 0.90;
sigmaA = 0.01;
sigmaU = 0.01;
sigmaG = 0.01;
nu = 0.8;
sc = 0.2;
t = 0.25;
AUX = ((1-alpha)*(1-1/Phi)/(1/beta - 1 + delta))^((1-alpha)/alpha);
Wss = AUX *alpha*(1-1/Phi);
Lss = ((1-sc-delta*AUX^(alpha/(1-alpha)))*sigmaL/(sigmaL-1)*omega*1/alpha*(1-1/Phi)^(-1))^(1/(-nu-1));
Kss = Lss*AUX^(1/(1-alpha));
Yss = Lss^(alpha)*Kss^(1-alpha);
Gss = sc*Yss;
Css = Yss - delta*Kss - Gss;
Rss = 1/beta;
TAXBAR = t;
Bss = (sc*Yss-TAXBAR)/(1-Rss+tau);
TAXss = TAXBAR + tau*Bss;
Iss = delta*Kss;
RKss = 1/beta - 1 + delta;
LAMss = 1/Css;
Ass = 1;
Uss = 1;
model;
UTIL = log(C) -omega/(1+nu)*L^(1+nu);
LAM = beta*LAM(+1)*R/PI(+1);
LAM = beta*LAM(+1)*(RK(+1) + (1-delta));
LAM = 1/C;
W = sigmaL/(sigmaL-1)*omega*L^(nu)*1/LAM;
Y = A*L^(alpha)*K(-1)^(1-alpha);
RK = (1-alpha)*MC*A*L^(alpha)*K(-1)^(-alpha);
W = alpha*MC*A*L^(alpha-1)*K(-1)^(1-alpha);
1 - phiP*(PI-1)*PI + beta*phiP*LAM(+1)/LAM*(PI(+1)-1)*Y(+1)/Y*PI(+1) - (1-MC)*Phi = 0;
B = R(-1)*B(-1)/PI + G - TAX;
TAX/TAXBAR = (B/Bss)^tau;
R/Rss = (PI)^(jotaPI)*(Y/Yss)^(jotaY)*U;
K = (1-delta)*K(-1) + I;
Y = C + I + G + phiP/2*(PI-1)^2*Y;
RR = R/PI(+1);
A = ((Ass)^(1-rhoA) )*( A(-1)^rhoA )*exp(eps_A);
U = ((Uss)^(1-rhoU) )*( U(-1)^rhoU )*exp(eps_U);
G = ((Gss)^(1-rhoG) )*( G(-1)^rhoG )*exp(eps_G);
end;
initval;
UTIL = log(Css) -omega/(1+nu)*Lss^(1+nu);
B = Bss;
PI = 1;
A = Ass;
U = Uss;
G = Gss;
MC = (Phi-1)/Phi;
TAX = TAXss;
R = Rss;
W = Wss;
L = Lss;
K = Kss;
Y = Yss;
C = Css;
LAM = LAMss;
RK = RKss;
I = Iss;
RR = Rss;
end;
steady;
shocks;
var eps_A = sigmaA;
var eps_U = sigmaU;
var eps_G = sigmaG;
end;
stoch_simul(periods=0,irf=20,order=1);
```